High linoleic waste sunflower oil: A distinctive recycled source of self-healing agent for smart metal coatings - Z. Baharom, Z. Baharom; H.Z. Abdullah, M.I. Idris, H.Z. Abdullah, M.I. Idris; Z.M.M. Ismail, Z.M.M. Ismail (Cel Press, 2023)
High Linoleic Waste Sunflower Oil (HLWSO) is a new self-healing agent viable to be encapsulated. Meanwhile, the unique mechanism behind the synthesis of microcapsules is deeply illustrated; the emulsification process of HLWSO by anionic surfactant and microencapsulation of HLWSO. In addition, the application of microencapsulated HLWSO in the coating matrix by the layering method is presented followed by a detailed explanation of the self-healing mechanism of a smart coating incorporating the polymerization mechanism of HLWSO developed by the diene structure. Microencapsulation of high linoleic waste sunflower oil (HLWSO) is a wall formation process in which urea-formaldehyde (UF) is attached with emulsified HLWSO to form a microcapsule. In this study, the HLWSO from recycled cooking oil is uniquely bonded with a diene structure, thus possessing the ability to dry fast and be encapsulated via the in-situ polymerization method. The microencapsulated HLWSO was characterized using Field Emission Scanning Electron Microscopy (FESEM) and Fourier Transformation Infra-Red Spectroscopy (FTIR). The optimum microcapsules synthesized from HLWSO resulted in a smooth shell structure with 2.88 μm diameter microcapsules at 0.31 μm shell thickness and 66% core content. It was demonstrated that increased stirring speed decreases the size, shell thickness, and core content of the microcapsules. The FTIR results indicated that HLWSO as a core, while urea-formaldehyde acted as a shell of microcapsules. The scratch on the coating matrix embedded with HLWSO was healed after five days. The corrosion rate of optimum sample was 0.0574 mm/year, with an optimum reduction of 58% from the reference sample. This study revealed that the HLWSO from recycled sources is a viable self-healing agent to be microencapsulated. The smart coating embedded with HLWSO also displayed self-healing performance, reduced corrosion rate and beneficial for the advancement of corrosion control technology.